KOMUNIKASI PEMASARAN KOMPASTV MELALUI MEDIA SOSIAL DALAM PERSAINGAN BISNIS - Noufal Helmy (Communicology: Jurnal Ilmu Komunikasi, 2019)
ABSTRACT The large number of television stations present in Indonesia gives its own color in the world of Indonesian broadcasting. KompasTV realizes that the rapid advances in information technology have an impact on the behavior of Indonesian people, especially for KompasTV glass screen lovers. Answering this challenge, KompasTV is present to greet loyal viewers in digital form on various social media. The purpose of this study was to find out how KompasTV marketing communications, using social media in business competition. This study uses new media theory and communication mix theory. The paradigm used is post-positivism with qualitative approaches and case study research methods. The research data collection technique was obtained using interview and observation techniques to the subjects of the KompasTV digital division research, and strengthened by KompasTV social media users. The research results obtained are that KompasTV marketing communication using social media (media mix) can expand its broadcast network, audiences on social media have similarities with KompasTV's target audience on social media, and can provide information to KompasTV social media users in the form of advertising promotions, content news, as well as programs that attract the attention and interest of the audience. In addition, using KompasTV social media wants to invite audiences on social media to switch to watching news content and programs offered by KompasTV both through live streaming and on the KompasTV television screen. Keywords: Marketing Communication, Social Media, Promotion, Business.